2016
DOI: 10.18203/2319-2003.ijbcp20161505
|View full text |Cite
|
Sign up to set email alerts
|

Awareness about generic drug prescription amongst practitioners: a knowledge attitude practice survey at rural set up

Abstract: Background: to evaluate the knowledge, attitude and practices regarding generic drugs prescription and the factors influencing it amongst practitioners at a rural set up. Methods: All the practitioners in the town, at both government and private settings were interviewed individually and the data was collected with the help of a self-administered, pre-validated and semi-structured questionnaire. Data were analysed to describe all variables and test any significant difference between the practitioners at govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
1
1
Order By: Relevance
“…76.92% of physicians had a positive attitude for Government role and also felt that there was a significant price difference between generic medicine and brand medicine. [9] In concurrence to our results, Kembhavi et al, 2014 demonstrated that 75% of doctors agreed that generic medicines are as effective and of better quality. 61.67% of doctors said that more awareness and education about prices of generic medicines should be made among doctors.…”
Section: Discussionsupporting
confidence: 91%
“…76.92% of physicians had a positive attitude for Government role and also felt that there was a significant price difference between generic medicine and brand medicine. [9] In concurrence to our results, Kembhavi et al, 2014 demonstrated that 75% of doctors agreed that generic medicines are as effective and of better quality. 61.67% of doctors said that more awareness and education about prices of generic medicines should be made among doctors.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding substitution of brands with generics in all conditions, the majority did not feel comfortable with that. This is in contrast with some other Indian studies like those by Tandel et al [23], Gupta et al [24], and Patil et al [28].…”
Section: Discussioncontrasting
confidence: 73%
“…In India, studies have been conducted at tertiary care settings at various states [22][23][24][25], while some studies were conducted on medical practitioners based on particular cities [26,27]. Some studies had included both [28,29].…”
Section: Discussionmentioning
confidence: 99%